Hydrodynamic Drivers and Morphological Responses on Small Coral Islands—The Thoondu Spit on Fuvahmulah, the Maldives - David, C. Gabriel; Schlurmann, Torsten (Frontiers in Marine Science, 2020)
Assessing the resilience of islands towards altered ocean climate pressures and providing robust adaptation measures requires an understanding of the interaction between morphological processes and the underlying hydrodynamic drivers. In this sense, this study presents changing sediment volumes on various temporal scales for the fringing reef island Fuvahmulah. Based on three field campaigns, conducted over 2 years, aerial imagery provides information on marine aggregates of the island’s beaches. In addition, high resolution climate reanalysis data serves as input into an empirical and a numerical approach. Together, both approaches describe the driving processes behind volumetric seasonal and interannual changes: On the one hand, the empirical method quantifies sediment transport rates for calcareous sediments over the whole time span of the data set by considering wind and swell waves from multiple directions. On the other hand, the numerical method gives insights into the complexity of currents induced by dominant wave components. Combining these methods facilitates hindcasting and predicting morphological changes under varying wave climate, assessing sediment pathways over the whole reef, and describing the seasonal and interannual evolution of the sand spit Thoondu. As a result, this study reveals sediment distribution on different spatio- temporal scales and elucidates their significance in the design of conventional and alternative low-regret coastal adaptation.